Shwachman–Bodian–Diamond syndrome (SBDS) protein deficiency impairs translation re-initiation from C/EBPα and C/EBPβ mRNAs - In, Kyungmin (Nucleic Acids Res, 2016)
Mutations in the Shwachman–Bodian–Diamond Syndrome (SBDS) gene cause Shwachman–Diamond Syndrome (SDS), a rare congenital disease characterized by bone marrow failure with neutropenia, exocrine pancreatic dysfunction and skeletal abnormalities. The SBDS protein is important for ribosome maturation and therefore SDS belongs to the ribosomopathies. It is unknown, however, if loss of SBDS functionality affects the translation of specific mRNAs and whether this could play a role in the development of the clinical features of SDS. Here, we report that translation of the C/EBPα and -β mRNAs, that are indispensible regulators of granulocytic differentiation, is altered by SBDS mutations or knockdown. We show that SBDS function is specifically required for efficient translation re-initiation into the protein isoforms C/EBPα-p30 and C/EBPβ-LIP, which is controlled by a single cis-regulatory upstream open reading frame (uORF) in the 5′ untranslated regions (5′ UTRs) of both mRNAs. Furthermore, we show that as a consequence of the C/EBPα and -β deregulation the expression of MYC is decreased with associated reduction in proliferation, suggesting that failure of progenitor proliferation contributes to the haematological phenotype of SDS. Therefore, our study provides the first indication that disturbance of specific translation by loss of SBDS function may contribute to the development of the SDS phenotype.